2015
DOI: 10.1108/maj-06-2015-1201
|View full text |Cite
|
Sign up to set email alerts
|

Transparency report disclosure by Australian audit firms and opportunities for research

Abstract: Purpose – The purpose of this study is to compare the information disclosed by leading Australian audit firms in their first-time audit firm transparency reports. Australia has mandated the preparation and release of transparency reports by audit firms in 2013 to provide better information to stakeholders about audit firms, their governance and their internal governance systems. These reports promote increased transparency regarding issues which are believed to contribute to audit quality. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 22 publications
0
50
0
2
Order By: Relevance
“…The introduction of transparency reporting in the European Union (EU), Australia, and Japan provides further support for an overall evaluation of the firm's quality control system effectiveness (IOSCO 2009). Both the EU's Eight Company Law Directive and the Australian Corporations Legislation Amendment (Audit Enhancement) Act 2012 include in the transparency reporting items a requirement to describe the firm's internal quality control system ("IQCS") and include a statement on the effectiveness of the IQCS (Fu, Carson, and Simnett 2015). The Japan CPA Act requires commensurate evaluation and disclosure related to the "performance of business operations and maintenance of service control framework" (IOSCO 2009;Fu et al 2015).…”
Section: Question-specific Commentarymentioning
confidence: 99%
“…The introduction of transparency reporting in the European Union (EU), Australia, and Japan provides further support for an overall evaluation of the firm's quality control system effectiveness (IOSCO 2009). Both the EU's Eight Company Law Directive and the Australian Corporations Legislation Amendment (Audit Enhancement) Act 2012 include in the transparency reporting items a requirement to describe the firm's internal quality control system ("IQCS") and include a statement on the effectiveness of the IQCS (Fu, Carson, and Simnett 2015). The Japan CPA Act requires commensurate evaluation and disclosure related to the "performance of business operations and maintenance of service control framework" (IOSCO 2009;Fu et al 2015).…”
Section: Question-specific Commentarymentioning
confidence: 99%
“…They examined the links between audit quality (proxied by the clients' earnings quality) and the reports issued by audit firms, but the researchers did not find a significant association. In the Australian context, Fu, Carson, and Simnett () compared the information disclosed by the 21 leading Australian audit firms in their first‐time TRs (issued in 2013) and they found that audit firms meet the minimum TR disclosure requirements, but have different approaches to governance in the areas that may affect audit quality.…”
Section: Background and Hypotheses Developmentmentioning
confidence: 99%
“…In the Australian context, Fu, Carson, and Simnett (2015) compared the information disclosed by the 21 leading Australian audit firms in their first-time TRs (issued in 2013) and they found that audit firms meet the minimum TR disclosure requirements, but have different approaches to governance in the areas that may affect audit quality.…”
Section: Related Research and Theoretical Approachmentioning
confidence: 99%
“…However, they find no association between the variations in the disclosure score and proxies of audit quality. Finally, Fu, Carson and Simnett [7] found that Australian audit firms do meet the minimum transparency report disclosure requirements, but have different approaches to governance in areas that may impact audit quality. These areas include: the internal quality control systems, independence practices, continuing education and partner remuneration structures.…”
Section: Review Of Transparency Report Literaturementioning
confidence: 99%
“…Also, the US Treasury Advisory Committee recommended increased transparency in the governance of audit firms. Specifically, the Committee suggested that audit firms with 100 or more public clients should produce transparency reports annually [7]. In 2014, European Union (EU) requirements for transparency reporting by audit firms complied with Regulation No.…”
Section: Transparency Report Of Audit Firmsmentioning
confidence: 99%